More Interaction Sites and Enhanced Fluorescence for Highly Sensitive Fluorescence Detection of Methamphetamine Vapor via Sidechain Terminal Functionalization of Conjugated Polymers. Issue 27 (21st July 2020) - Yu, Yaguo; Xu, Wei; Wang, Tan; Fu, Yanyan; Cao, Huimin; He, Qingguo; Cheng, Jiangong
Abstract: A strategy of sidechain terminal functionalization was proposed to further improve the sensitivity of MA vapor detection. In this work, three fluorescent conjugated polymers (CPs) were synthesized by introducing NHBoc group at the end of the side chains and characterized by GPC, 1 H NMR, FT‐IR and 19 F NMR. The test results show that the introduction of the NHBoc group reduces the effect of aggregation‐caused quenching (ACQ), thereby improving the fluorescence intensity and fluorescence quantum efficiency of CPs. Secondly, it increases the interaction sites for MA capture and expands the scope of the interaction, thereby increasing the contact probability and interaction between the CPs and MA. Thirdly, the morphology of the CPs has also changed, especially the polymer containing 5‐fluoro‐2, 1, 3‐benzothiadiazole (1F‐2NHBoc‐CP), whose film has a network‐crosslinked porous structure, which is conducive to the enrichment and penetration of N ‐methylphenethylamine (MPEA, a simulant of MA) vapor at low concentration. All these effects contribute to efficient fluorescence quenching, so the 1F‐2NHBoc‐CP can achieve more than 74% fluorescence quenching within 30 s. Taking fluorescence quenching to 1% as the detection limit, MPEA vapor with an actual concentration of 41 ppt can be detected, and its sensitivity is increased by about 25 folds relative to the NHBoc‐free counterpart polymer. Furthermore, it showed a linear correlation with MPEA vapor in the range of 41 ppt to 16 ppm, which spanned five orders of magnitude. This strategy will find a great potential in developing highly sensitive fluorescent probe for dangerous chemical vapor detection. Abstract : Through the functionalization of the side chain (NHBoc), not only the network cross‐linked porous film material with improved fluorescence quantum yield is obtained, but also more sites are introduced to realize the fluorescence detection of the N ‐methylphenethylamine (MPEA, a simulant of MA) vapor with a real concentration of 41 ppt [the polymer 8 containing 5‐fluoro‐2, 1, 3‐benzothiadiazole and NHBoc groups (1F‐2NHBoc‐CP)], and through the characterization method and quantum chemical calculation to prove the interaction process.